Low-dose aspirin in systemic lupus erythematosus pregnancy: impact on pregnancy outcomes and optimal management - Abe, Saori; Tsuboi, Hiroto; Yagishita, Mizuki; Ohyama, Ayako; Kitada, Ayako; Miki, Haruka; Asashima, Hiromitsu; Kondo, Yuya; Matsumoto, Isao (Frontiers in Lupus, 2024)
Systemic lupus erythematosus (SLE) presents unique challenges in pregnancy management due to the increased risk of pregnancy-related complications and potential for disease flare during pregnancy. In all SLE pregnancies, low-dose aspirin (LDA) is recommended to reduce the risk of preeclampsia, a significant pregnancy complication, despite limited evidence specifically targeting this population. This study aimed to evaluate the efficacy of LDA in improving pregnancy outcomes among patients with SLE and to explore the optimal dosage and timing of LDA administration. We conducted a retrospective single-center study including 75 pregnancies, the majority of which were planned except for three unplanned cases. Adverse pregnancy outcomes (APOs) were observed in 32 pregnancies (42.6%), with low birth weight being the most frequent (n = 25, 33.3%), followed by preeclampsia (n = 16, 21.3%). In our study with a limited sample size, no significant differences in APOs were found between the LDA-prescribed and non-prescribed groups. However, within the LDA prescribed group, earlier initiation before 6 weeks of gestation, was associated with significantly higher birth weights (p = 0.01) and lower rates of early onset preeclampsia (p = 0.04) compared to later administration. Additionally, a daily 100 mg dose was more beneficial than an 80 mg dose in improving birth weight (p = 0.002) and reducing the frequency of APOs (p = 0.01). Our study highlights the necessity of assessing individual risk when prescribing LDA in lupus pregnancies and the potential benefits of early initiation and optimal dosing of LDA in improving pregnancy outcomes.